FEEDBACK: DIFFERENT CONCEPTS AND PRACTICES IN A CULTURALLY DIFFERENT ENVIRONMENT-FACULTY PERCEPTIONS - Ahsan Malik (Army Medical College Rawalpindi, 2021)
Objective: To explore the faculty perceptions regarding the phenomenon of feedback and its‟ practices in a traditional undergraduate dental college in Pakistan.